Actors in Preservation Local Wisdom: Mangure Lawik for Sustaining Marine Resources - Sihombing, Dwi Agustiani; Umar, Zulkarnain; Anugerah, Tirta; Adiprayoga, Shofian Nanda; Mahaji, Toga (International Journal of Marine Engineering Innovation and Research, 2025)
Mangure Lawik is a maritime hospitality activity developed by the ancestors of the Sibolga community and has been passed down continuously from one generation to the next. However, some people in Sibolga have experienced changes following the wave of modernization and have begun to abandon their customs. This paper aims to examine the history of Mangure Lawik, analyze the roles, interests, and influences of each stakeholder, and see the impact of this tradition on marine resources using ethnographic methods assisted by Stakeholder Analysis, it was concluded that the history of Mangure Lawik is divided into three periods (early, middle & present). This study also shows that there are 17 stakeholders consisting of 5 main stakeholders, 6 primary stakeholders, and 6 secondary stakeholders. The role of stakeholders is divided into four categories, namely: Policy Makers, Coordinators, Facilitators, and Implementers, where each stakeholder has carried it out well so that the Mangure Lawik tradition can continue. In its implementation, Mangure Lawik impacts the diversity of coastal and marine resources, because it indirectly invites the community to manage and protect coastal and marine resources, maintain the balance of aquatic ecosystems, and prevent coastal environmental pollution.